A Therapeutic Action of Vatari Guggulu in Amavata, Sandhigata Vata & Grudhrasi - Geeta Vishwanath Sathavane; Shilpa Gabhane; Madhulika Tiwari; Komal Kedar; Seema Thakre; Shailesh Nagpure (Indian Journal of Forensic Medicine & Toxicology, 2021)
Drug (Ausadha) is a part of quadruped of the treatment, which has been placed next to the physician. Thecomprehensive knowledge of the drug is very important to physician because without knowledge of drugpatient cannot be treated properly. Vatari guggulu is such herbal remedy mentioned in the ancient ayurvedictexts of Bhaishajya Ratnavali Amavata chikitsa prakarana for the treatment of various diseases like Samavata,Katishool (Low back ache), Grudhrasi (Sciatica), Khanja, Pangu, Vatarakta (Gout) ,Shotha, Daha ( Relivesburning sensation) and Koshtukshirsha. It having Vatashamaka, Kaphashamaka, Aamapachana, dipana,Vedanasthapana and Rasayana properties. Various study is carried out to evaluate the efficacy of drug VatariGuggulu in diseases like Amavata,Sandhigata Vata and Grudhrasi and significant results were obtained.Thepresent review article aim to evaluate the Theurapeutic action of Vatari Guggulu in aamavata,SandhigataVata,Grudhrasi.